The Performance of Pomoghono Ritual on the Muna Ethnic Community at Muna Regency, Southeast Province, Indonesia - Aso, La; Taena, La; Karsadi, .; Tamburu, La; Diysi, La; Salimu, La (Advances in Social Sciences Research Journal, 2021)
The Muna ethnic community comprises a variety of traditions with the pomoghono ritual amongst those still practiced to date. This ritual is related to the life cycle of each member of the community, including death. The purpose of this research is to analyze the performance and symbolic meaning of the pomoghono ritual in the Muna ethnic community by using the theory of semiotics proposed by C.S. Pierce. Data were collected from primary and secondary sources through (1) observation, (2) in-depth interviews, and (3) documentation. The collected data were analyzed using descriptive-qualitative and interpretive analysis. The results showed that the ritual performance in Muna community started with the following: (a) the installation of permanent gravestones in the ritualized grave; (b) watering, burning incense, and reciting prayers; (c) reciting the haroa turantana prayer at the family home of the corpse. It also showed that the ritual consists of a variety of symbolic meanings which are directly related to the human body as seen from the contents of the haroa turuntana offerings.